Preparation method of high-adaptability ultrahigh-strength duct piece concrete admixture
By introducing heterocyclic rings on the side chain of the polycarboxylic acid water reducing agent, and combining a variety of polycarboxylic acid mother liquor and nanomaterials, the stirring and coagulation process of concrete is optimized, and the problems that are difficult to meet in the existing technology are solved, and efficient and stable ultra-high strength concrete production is achieved.
Patent Information
- Application Number
- CN202411809610.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The existing technology is difficult to meet the high strength, crack resistance and stability requirements of concrete in high-rise buildings, large-span bridges and wind power tower bases. Especially in major concrete structural projects used in harsh environments, there are problems such as excessive viscosity, rapid loss, insufficient early strength, and many cracks.
A highly adaptable ultra-high strength tube sheet concrete admixture is adopted to introduce heterocyclic rings on the side chain of the polycarboxylic acid water reducer to improve the steric hindrance and adsorption capacity of cement particles. Combined with polycarboxylic acid fast dispersion and viscosity reduction mother liquor, polycarboxylic acid early strength mother liquor, polycarboxylic acid comprehensive mother liquor, nano early strength agent, functional defoaming agent and temperature-inhibiting and anti-cracking agent, the stirring time, settling time and early strength of the concrete are optimized.
It achieves excellent working performance of concrete, high early strength, good crack resistance, apparent bubble-free and beautiful decorative effect, and improves the adaptability to cements of different abrasive agents, meeting the stable production needs of ultra-high strength concrete.
Smart Images

Figure QLYQS_1 
Figure BDA0005180226310000041 
Figure BDA0005180226310000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete modifiers, and specifically relates to a method for preparing a highly adaptable ultra-high-strength segment concrete admixture. Background Art
[0002] With the development of modern architecture towards higher and more personalized development, such as high-rise buildings, large-span bridges, offshore oil platforms, wind turbine tower bases, wind turbine hybrid tower segments, etc., C15-C60 concrete can no longer fully meet the needs of the project, thus putting forward high-strength and ultra-high-strength requirements for concrete performance. As well as major concrete structure projects used in harsh environments, not only are the construction difficult, the use environment is harsh, and maintenance is difficult, but also the concrete is required to have good construction performance, try not to produce defects during pouring, and have good durability and long service life, so higher quality requirements are put forward for concrete.
[0003] As a sustainable natural resource, wind energy has the advantages of being widely distributed, safe, clean, and environmentally friendly. The industrialization and scale of related development projects are developing rapidly. With the increase in the power of wind turbines and the expansion of their application areas, wind power equipment is constantly iterating and upgrading, which poses new challenges to the strength, height, durability, and reliability of its main supporting structure - the concrete tower.
[0004] During the production process of high-strength wind power tower concrete, especially C80 and above grades, many problems are often encountered, such as excessive viscosity, rapid loss and other workability problems, difficult pouring, and high loss; the early strength of the entity does not meet the standard and cannot be lifted, delaying the construction period; the strength increases slowly, and it is difficult to reach the design strength in 28d; there are many cracks in the specimens, which has a certain impact on the safety of the wind tower, etc.
[0005] Cement is an important cementing material in concrete. There are many cement manufacturers and many types of grinding aids, mainly amines. The working performance of concrete will change to varying degrees with different types of cement grinding aids. Therefore, admixtures with strong adaptability to the use of cements with different grinding aids have a stronger effect on the performance stability of segment concrete.
[0006] Therefore, it is of great significance to develop an admixture required for ultra-high-strength concrete with excellent working performance, high early strength, crack resistance, apparent bubble-free, beautiful appearance, good decorative effect and strong adaptability. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing a highly adaptable ultra-high-strength segment concrete admixture to solve the problems existing in the prior art.
[0008] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a highly adaptable ultra-high strength segment concrete admixture, comprising 16%-20% of polycarboxylic acid water-reducing mother liquor, 10%-12% of polycarboxylic acid fast-dispersing viscosity-reducing mother liquor, 6%-10% of polycarboxylic acid early strength mother liquor, 10%-16% of polycarboxylic acid comprehensive mother liquor, 2% of polycarboxylic acid short-term collapse-retaining mother liquor, 5%-15% of nano early strength agent, 0.1% of functional defoaming agent, and 5%-10% of temperature-inhibiting and anti-cracking agent, wherein the percentages of the compounds are percentages by weight and the balance is water.
[0009] A method for preparing a highly adaptable ultra-high strength segment concrete admixture comprises the following steps:
[0010] Step 1: Add nano early strength agent, temperature inhibitor and anti-cracking agent, functional defoamer and water into a stirring tank and stir for 10 minutes to obtain a uniform solution;
[0011] Step 2: Add polycarboxylic acid water-reducing mother liquor, polycarboxylic acid fast-dispersing viscosity-reducing mother liquor, polycarboxylic acid early-strength mother liquor, polycarboxylic acid comprehensive mother liquor, and polycarboxylic acid short-term collapse-retaining mother liquor to the uniform solution obtained in step 1 in sequence, and stir for 30 minutes to obtain an ultra-high-strength segment concrete admixture.
[0012] Compared with the prior art, the present invention has the following beneficial effects:
[0013] The highly adaptable ultra-high strength segment concrete admixture prepared in the present invention introduces heterocycles on the side chains of the water reducer molecules, which is beneficial to improving steric hindrance, reducing the degree of freedom of the main chain, and improving the adsorption of cement particles by the small molecule carboxyl groups of the side chains of the water reducer, which is beneficial to the rapid dispersion of the cement slurry. The low sensitivity of the polycarboxylic acid comprehensive mother liquor and the combination of the polycarboxylic acid short-term collapse-preserving mother liquor with the comprehensive mother liquor are used to solve the problems of early losses and temperature; in order to solve the problem of long setting time, the high water reduction rate of the polycarboxylic acid water-reducing mother liquor and the high efficiency collapse-preserving performance of the comprehensive mother liquor with the short-term collapse-preserving mother liquor are used, and the amount of polycarboxylic acid collapse-preserving mother liquor in the slurry is increased, thereby shortening the setting time;
[0014] In order to solve the problem of cracks easily occurring in the embedded metal holes, the early strength of the specimens is increased and the risk of cracking due to temperature rise shrinkage is reduced, thereby reducing the difference in strength between the embedded holes and the embedded metal and reducing the risk of cracking.
[0015] The polyether-modified silicone defoamer and hydrophobic nano-silica in the functional defoamer are used together to effectively control the bubbles in the concrete. Due to the presence of hydrophobic nano-silica, the polyether-modified silicone can diffuse faster on the air-water interface in the foaming liquid, thereby improving the dispersion efficiency of the polyether-modified silicone and the efficiency of eliminating bubbles.
[0016] It is necessary to have better adaptability to cement with different types of grinding aids, small fluctuation in dosage and small loss difference to meet the stable production of segment concrete.
[0017] When the highly adaptable ultra-high strength segment concrete admixture prepared by the present invention is added, the prepared high-strength concrete has excellent working performance, high early strength and good crack resistance; the prepared segment has no bubbles on the surface, so it is more beautiful and has a good decorative effect.
[0018] The method for preparing the highly adaptable ultra-high-strength segment concrete admixture of the present invention has a simple process, uses affordable raw materials, and is convenient for mass production. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below.
[0020] A highly adaptable ultra-high strength segment concrete admixture comprises 16%-20% of polycarboxylic acid water-reducing mother liquor, 10%-12% of polycarboxylic acid fast-dispersing viscosity-reducing mother liquor, 6%-10% of polycarboxylic acid early strength mother liquor, 10%-16% of polycarboxylic acid comprehensive mother liquor, 2% of polycarboxylic acid short-term slump-retaining mother liquor, 5%-15% of nano early strength agent, 0.1% of functional defoaming agent, and 5%-10% of temperature-inhibiting and anti-cracking agent. The percentages of the compounds are percentages by weight, and the balance is water.
[0021] The polycarboxylic acid water-reducing mother liquor is of the EPEG-2400-3000 type, with a water reduction rate of ≥32% and a solid content of 50%; the polycarboxylic acid fast-dispersing viscosity-reducing mother liquor is of the EPEG-1600-2000 type, with a water reduction rate of ≥20% and a solid content of 50%; the polycarboxylic acid early-strength mother liquor is of the TPEG-4000-5000 type, with a water reduction rate of ≥25% and a solid content of 50%; the polycarboxylic acid comprehensive mother liquor is of the EPEG-2400-3000 type, with a water reduction rate of ≥20% and a solid content of 50%; the polycarboxylic acid short-term slump-retaining mother liquor is of the EPEG-2000-2400 type, with a water reduction rate of ≥10%.
[0022] The polycarboxylic acid fast dispersing viscosity-reducing mother solution comprises an unsaturated polyether macromonomer and an unsaturated heterocyclic carboxylic acid monomer, wherein the molar ratio of the heterocyclic unsaturated carboxylic acid monomer to the unsaturated polyether macromonomer is 1.2-1.8:1;
[0023] The general structure formula of polycarboxylic acid fast dispersing viscosity reducing mother solution is shown in Formula 1:
[0024]
[0025] Wherein, R is a furan ring or a thiophene ring, a, b, c are positive integers, and a, b, c are selected from 1 to 30.
[0026] The nano early strength agent is a CSH crystal nucleus early strength agent; a liquid mixture of a functional defoamer polyether modified silicone defoamer and hydrophobic nano silicon dioxide in a mass ratio of 20-45:55-80;
[0027] A method for preparing a highly adaptable ultra-high strength segment concrete admixture comprises the following steps:
[0028] Step 1: Add nano early strength agent, temperature inhibitor and anti-cracking agent, functional defoamer and water into a stirring tank and stir for 10 minutes to obtain a uniform solution;
[0029] Step 2: Add polycarboxylic acid water-reducing mother liquor, polycarboxylic acid fast-dispersing viscosity-reducing mother liquor, polycarboxylic acid early-strength mother liquor, polycarboxylic acid comprehensive mother liquor, and polycarboxylic acid short-term collapse-retaining mother liquor to the uniform solution obtained in step 1 in sequence, and stir for 30 minutes to obtain an ultra-high-strength segment concrete admixture.
[0030] Example 1
[0031] A highly adaptable ultra-high strength segment concrete admixture, comprising 16% polycarboxylic acid water-reducing mother liquor, 12% polycarboxylic acid fast-dispersing viscosity-reducing mother liquor, 10% polycarboxylic acid early strength mother liquor, 16% polycarboxylic acid comprehensive mother liquor, 2% polycarboxylic acid short-term collapse-retaining mother liquor, 5% nano early strength agent, 0.1% functional defoaming agent, 5% temperature-suppressing and anti-cracking agent, and 33.9% water, wherein the compound percentages are weight percentages.
[0032] Containing 35g of furan heterocyclic unsaturated carboxylic acid monomer and 415g of unsaturated polyether EPEG-1800 macromonomer, in the presence of an initiator, a reducing agent and a chain transfer agent system, the reaction is carried out at room temperature for 60 minutes and the temperature is kept for 60 minutes to prepare a polycarboxylic acid fast-dispersing viscosity-reducing mother solution.
[0033] The preparation method of a highly adaptable ultra-high strength segment concrete admixture comprises the following steps:
[0034] Step 1: Add nano early strength agent, temperature inhibitor and anti-cracking agent, functional defoamer and water into a stirring tank and stir for 10 minutes;
[0035] Step 2: Add polycarboxylic acid water-reducing mother liquor, polycarboxylic acid fast-dispersing viscosity-reducing mother liquor, polycarboxylic acid early-strength mother liquor, polycarboxylic acid comprehensive mother liquor, polycarboxylic acid short-term collapse-retaining mother liquor, and water to the uniform solution obtained in step 1 in sequence, and stir for 30 minutes to obtain a highly adaptable ultra-high-strength segment concrete admixture.
[0036] Example 2
[0037] Different from the above-mentioned Example 1, a highly adaptable ultra-high strength segment concrete admixture comprises 18% polycarboxylic acid water-reducing mother liquor, 12% polycarboxylic acid fast-dispersing viscosity-reducing mother liquor, 10% polycarboxylic acid early strength mother liquor, 14% polycarboxylic acid comprehensive mother liquor, 2% polycarboxylic acid short-term collapse-retaining mother liquor, 10% nano early strength agent, 0.1% functional defoaming agent, 5% temperature inhibitor and anti-cracking agent, and 28.9% water, and the percentages of the compounds are by weight.
[0038] Example 3
[0039] The difference from the above-mentioned embodiment 1-2 is that the polycarboxylic acid water-reducing mother solution is 20%, the polycarboxylic acid fast-dispersing viscosity-reducing mother solution is 10%, the polycarboxylic acid early-strengthening mother solution is 6%, the polycarboxylic acid comprehensive mother solution is 10%, the polycarboxylic acid short-term slump-retaining mother solution is 2%, the nano early-strengthening agent is 15%, the functional defoaming agent is 0.1%, the temperature-suppressing and anti-cracking agent is 10%, and the water is 26.9%. The percentages of the compounds are weight percentages.
[0040] Comparative Example 1
[0041] The difference from the above-mentioned Examples 1-3 is that the polycarboxylic acid water-reducing mother liquor is 18%, the polycarboxylic acid fast-dispersing viscosity-reducing mother liquor is 12%, the polycarboxylic acid early-strengthening mother liquor is 10%, the polycarboxylic acid comprehensive mother liquor is 14%, the polycarboxylic acid short-term slump-retaining mother liquor is 2%, the nano early-strengthening agent is 2%, the functional defoaming agent is 0.1%, the temperature-suppressing and anti-cracking agent is 2%, and the water is 41.9%. The percentages of the compounds are by weight.
[0042] Comparative Example 2
[0043] High-strength mixed pipe concrete admixture I produced by Leizhi Holding Group Co., Ltd.
[0044] Comparative Example 3
[0045] High-strength mixed pipe concrete admixture II produced by Jiangsu Subote New Materials Co., Ltd.
[0046] Test example
[0047] The water reducing agents in the embodiments and comparative examples were tested for concrete mixing, and the concrete performance test was conducted in accordance with GB8076-2008 "Concrete Admixtures". Esheng cement was selected, and the water-cement ratio was 0.22%, see Table 1.
[0048] The concrete test batch number is C80, and its collapse, hydration temperature rise, and appearance of the molded sample are measured; its adaptability to different cements, including dosage, state, strength change, etc. The fineness modulus of the machine-made sand in the concrete is 2.6, the crushed stone is a continuously graded crushed stone with a particle size of 5-25mm, and the polycarboxylate water reducer is added in an amount of 1.7-2.2wt%.
[0049] Table 1C80 concrete mix ratio
[0050] cement Microbeads Mineral powder Silica Fume Machine-made sand aggregate water 380 100 60 50 630 1050 130
[0051] Table 2 Concrete performance data C30
[0052]
[0053]
[0054] It can be seen from the concrete performance data in Table 2 that the performance of the water reducers in Examples 1-3 is better than that of the water reducers in Comparative Examples 1-3, mainly in terms of viscosity, 1d strength, hydration temperature rise peak, and appearance of the specimens.
[0055] Table 3 Data table of different cement adaptability
[0056]
[0057]
[0058] It can be concluded from Table 3 that the water reducers in Example 2 and Comparative Example 3 are compared, and concrete tests are carried out on cements such as Esheng Cement, Conch Cement, Jidong Cement, Huaxin Cement, and Hongshi Cement. The dosage of Example 2 varies from 0.1% to 0.2%, and the dosage of Comparative Example 3 varies from 0.1% to 0.5%. The collapse, working performance, and 1d strength stability are all better than those of Comparative Example 3, and all meet the requirements, proving that the admixture in the present application has good adaptability to different cements.
[0059] The present invention introduces heterocyclic rings into the side chains of water-reducing agent molecules, which is beneficial to improving steric hindrance, reducing the degree of freedom of the main chain, improving the adsorption of cement particles by the small molecular carboxyl groups of the side chains of the water-reducing agent, and facilitating the rapid dispersion of cement slurry. Taking advantage of the characteristics of fast dispersion speed and good viscosity reduction effect of the polycarboxylic acid fast dispersion slurry mother liquid, the mixing time of ultra-high strength concrete is shortened from 300 seconds to 180 seconds, and the collapse of concrete is shortened from 15 seconds to less than 8 seconds;
[0060] Ultra-high-strength concrete segments belong to the category of prefabricated components. The concrete slump requirement is low, generally 160±20mm. Low-slump concrete is prone to problems such as rapid early loss and high sensitivity to dosage. The low sensitivity of polycarboxylic acid comprehensive mother liquor and the combination of polycarboxylic acid short-term slump-preserving mother liquor and comprehensive mother liquor are used to solve the early loss and temperature problems. In order to solve the problem of long setting time, the high water reduction rate of polycarboxylic acid water-reducing mother liquor, the efficient slump-preserving performance of the comprehensive mother liquor combined with the short-term slump-preserving mother liquor, and the amount of polycarboxylic acid slump-preserving mother liquor in the slurry body are used to shorten the setting time.
[0061] In order to solve the problem of early strength, nano early strength agent is added to improve the 16h strength to meet the requirements of lifting and demoulding; in order to solve the problem of cracks, the use of temperature-suppressing and anti-cracking agent can reduce the peak value of concrete hydration heat release, reduce the concrete temperature shrinkage stress, and reduce the risk of concrete temperature rise shrinkage cracking. In order to solve the problem of cracks easily occurring at the embedded metal holes, the early strength of the specimens is increased and the risk of temperature rise shrinkage cracking is reduced, thereby reducing the strength difference between the embedded holes and the embedded metal, and reducing the risk of cracking.
[0062] The polyether-modified silicone defoamer and hydrophobic nano-silica in the functional defoamer are used to effectively control the bubbles in the concrete. First, the polyether-modified silicone defoamer is mainly composed of polyether with strong anti-foaming ability and dimethyl silicone oil with strong hydrophobicity and rapid bubble breaking. It has the characteristics of low surface tension, rapid defoaming, and long anti-foaming time, and has a good effect on eliminating bubbles in concrete. Second, the hydrophobic nano-silica has a small particle size and high surface energy, which enables it to form a huge force to adsorb bubbles. The "needle tip" effect of nano-silica adsorbs and impacts bubbles to create weak points and accelerate the rupture of bubbles. Third, polyether-modified silicone and hydrophobic nano-silica together attack the bubbles. With the presence of hydrophobic nano-silica, polyether-modified silicone can diffuse faster on the air-water interface in the foaming liquid, improve the dispersion efficiency of polyether-modified silicone, and improve the efficiency of bubble elimination.
[0063] In view of the influence of cements with different grinding aids on the working performance of concrete, the ultra-high-strength segment concrete admixture of the present invention has better adaptability to cements with different grinding aids, small fluctuation in dosage, small loss difference, etc., to meet the stable production of segment concrete;
[0064] It can solve the problems of great construction difficulty caused by the poor workability of ultra-high-strength concrete, inability to demould due to insufficient early strength, local cracks in the segments, and many bubbles in the segments, etc., improve construction efficiency, reduce production energy efficiency, reduce or avoid production quality risks, and meet the needs of low-carbon green development.
[0065] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention.
Claims
1. A highly adaptable ultra-high strength segment concrete admixture, characterized in that: Polycarboxylic acid water-reducing mother liquor 16%-20%, polycarboxylic acid fast-dispersing viscosity-reducing mother liquor 10%-12%, polycarboxylic acid early-strengthening mother liquor 6%-10%, polycarboxylic acid comprehensive mother liquor 10%-16%, polycarboxylic acid short-term slump-retaining mother liquor 2%, nano early-strengthening agent 5%-15%, functional defoaming agent 0.1%, temperature-inhibiting and anti-cracking agent 5%-10%, the percentages of the compounds are percentages by weight, and the balance is water.
2. A highly adaptable ultra-high strength segment concrete admixture according to claim 1, characterized in that: Polycarboxylic acid water-reducing mother liquor 16%, polycarboxylic acid fast-dispersing viscosity-reducing mother liquor 12%, polycarboxylic acid early-strengthening mother liquor 10%, polycarboxylic acid comprehensive mother liquor 16%, polycarboxylic acid short-term slump-retaining mother liquor 2%, nano early-strengthening agent 5%, functional defoaming agent 0.1%, temperature-inhibiting and anti-cracking agent 5%, the percentages of the compounds are percentages by weight, and the balance is water.
3. A highly adaptable ultra-high strength segment concrete admixture according to claim 2, characterized in that: Polycarboxylic acid water-reducing mother liquor 18%, polycarboxylic acid fast-dispersing viscosity-reducing mother liquor 12%, polycarboxylic acid early-strengthening mother liquor 10%, polycarboxylic acid comprehensive mother liquor 14%, polycarboxylic acid short-term slump-retaining mother liquor 2%, nano early-strengthening agent 10%, functional defoaming agent 0.1%, temperature-inhibiting and anti-cracking agent 5%, the percentages of the compounds are weight percentages, and the balance is water.
4. A highly adaptable ultra-high strength segment concrete admixture according to claim 3, characterized in that: Polycarboxylic acid water-reducing mother liquor 20%, polycarboxylic acid fast-dispersing viscosity-reducing mother liquor 10%, polycarboxylic acid early-strengthening mother liquor 6%, polycarboxylic acid comprehensive mother liquor 10%, polycarboxylic acid short-term slump-retaining mother liquor 2%, nano early-strengthening agent 15%, functional defoaming agent 0.1%, temperature-inhibiting and anti-cracking agent 10%, the percentages of the compounds are percentages by weight, and the balance is water.
5. A highly adaptable ultra-high strength segment concrete admixture according to claim 4, characterized in that: The polycarboxylic acid water-reducing mother liquor is of the EPEG-2400-3000 type, with a water reduction rate of ≥32% and a solid content of 50%; the polycarboxylic acid fast-dispersing viscosity-reducing mother liquor is of the EPEG-1600-2000 type, with a water reduction rate of ≥20% and a solid content of 50%; the polycarboxylic acid early-strength mother liquor is of the TPEG-4000-5000 type, with a water reduction rate of ≥25% and a solid content of 50%; the polycarboxylic acid comprehensive mother liquor is of the EPEG-2400-3000 type, with a water reduction rate of ≥20% and a solid content of 50%; the polycarboxylic acid short-term slump-retaining mother liquor is of the EPEG-2000-2400 type, with a water reduction rate of ≥10%.
6. A highly adaptable ultra-high strength segment concrete admixture according to claim 5, characterized in that: The polycarboxylic acid fast dispersing viscosity-reducing mother solution comprises an unsaturated polyether macromonomer and an unsaturated heterocyclic carboxylic acid monomer, wherein the molar ratio of the heterocyclic unsaturated carboxylic acid monomer to the unsaturated polyether macromonomer is 1.2-1.8:1; The general structure formula of polycarboxylic acid fast dispersing viscosity reducing mother solution is shown in Formula 1: Wherein, R is a furan ring or a thiophene ring, a, b, c are positive integers, and a, b, c are selected from 1 to 30.
7. A highly adaptable ultra-high strength segment concrete admixture according to claim 6, characterized in that: The nano early strength agent is a CSH crystal nucleus early strength agent; a liquid mixture of a functional defoamer polyether modified silicone defoamer and hydrophobic nano silicon dioxide in a mass ratio of 20-45:55-80.
8. A method for preparing a highly adaptable ultra-high strength segment concrete admixture according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: Add nano early strength agent, temperature inhibitor and anti-cracking agent, functional defoamer and water into a stirring tank and stir for 10 minutes to obtain a uniform solution; Step 2: Add polycarboxylic acid water-reducing mother liquor, polycarboxylic acid fast-dispersing viscosity-reducing mother liquor, polycarboxylic acid early-strength mother liquor, polycarboxylic acid comprehensive mother liquor, and polycarboxylic acid short-term collapse-retaining mother liquor to the uniform solution obtained in step 1 in sequence, and stir for 30 minutes to obtain an ultra-high-strength segment concrete admixture.
Citation Information
Patent Citations
Viscosity reduction type polycarboxylate superplasticizer used for high-strength concrete
CN106431060A
Low-slump early strength type polycarboxylate superplasticizer master batch for prefabricated part
CN106749972A
Prefabricated member concrete and curing method thereof
CN110698120A
Polycarboxylic acid high-performance pumping aid and production process thereof
CN111943561A
Preparation method of high-solid-content early-strength polycarboxylic acid slump retaining agent
CN114716622A